The end of an illusion - Joseph Vogl (Finance and Society, 2015)
Mainstream economics must be conceived of as a sort of 'dangerous' knowledge - because its models (like the idea of efficient markets) offer no explanation for the regularity of crises and crashes in financial markets in the last decades; and because these models were also employed in the implementation and justification of these very markets. Just as the Lisbon earthquake of 1755 once shook modern theodicy to its foundations, so the financial tremors of the last twenty years threaten to undermine the scientific status of economic theory. What is at issue is nothing less than the validity, possibility, and tenability of a liberal or capitalist oikodicy, a theodicy of the economic universe. It is likely that we are dealing here with one of the greatest and most fatal of errors of modern economics.
Keywords: 300